3D Modelling of Meteorite from Astomulyo Village, Lampung, Indonesia by Close Range Photogrammetry (CRP) Methods. Issue 1 (1st July 2022) - Harbowo, D G; Sitorus, J H; Agustina, L K; Muztaba, R; Julian, T; Malasan, H L
Abstract: This research was conducted to 3D model our meteorite collection based on photo-capturing. This meteorite are from Astomulyo, Central Lampung, Indonesia. It entry the earth's atmosphere and was found on January 28, 2021. The chance of object degradation nearly appears over time, so It is very urgent to obtain the 3D model of the object for further research necessary. 3D modelling was carried out using a non-metric camera to conduct the close-range photogrammetry method. It applies to modelling the objects based on photo data using the concept of collinearity by using a central projection system on the camera to record. The collinearity will produce an object point between the camera center and the object cloud point. Hence, this process forms the object model from the appropriate image projection, the tie point with the triangular irregular network model. As a result, it produces the DTM (Digital Terrain Model) object formation using stand-alone photogrammetric software, raster graphics, and 3D modelling software.